The Use of Community-Based Interventions in Reducing Morbidity from the Psychological Impact of Conflict-Related Trauma Among Refugee Populations: A Systematic Review of the Literature - Williams, M.; Thompson, Sandra (Springer, 2011)
With large numbers of refugee arrivals and numerous barriers to accessing services it is especially important that resources are efficiently and effectively directed to address the health needs of refugees. Ten databases were utilised to conduct the review, returning 156 titles which were assessed for validity based on specified criteria. The 14 critically appraised articles included in this review consist of experimental research and discussions on best practice. Articles consistently demonstrated the benefit of community-based mental health service in improving mental health outcomes. Themes of cultural awareness, language, setting, and post-migration stressors emerged across the articles. In addition, the studies also point to the gaps in research of a longitudinal nature and ones that deal with scattered populations post migration. Community based interventions proved valuable for improving the mental health of refugees. However, additional interventions and evaluations are required to draw consistent and conclusive judgments on best practice in dealing with refugee mental health issues.